Risk-Based Capital Requirements for Banks and International Trade - Demir, Banu; Michalski, Tomasz K.; Ors, Evren (Review of Financial Studies, 2017)
We test the trade finance channel of exports by controlling for the bank credit channel. Using Turkey’s July 2012 adoption of Basel II as a quasi-natural experiment, we examine whether shocks to trade financing costs affect exports. With data for 16,662 Turkish exporters shipping 2,888 different products to 158 countries, we find that the share of letters-of-credit-based exports decreases (increases) when the associated risk weights for counterparty exposure increase (decrease) after the adoption of Basel II. However, growth of firm-product-country-level exports remains unaffected. Trade financing might have a lesser role in exports than previously suggested by the previous literature. Received October 26, 2014; editorial decision March 15, 2017 by Editor Philip Strahan.